In the Shadow of the Green Revolution: Constrained Spatial Imaginaries and Smallholder Farming in Guatemala's Pacific Lowlands. Issue 2 (4th March 2023) - Schmook, Birgit; Radel, Claudia; Carte, Lindsey; Johnson, Richard L.
Abstract : Much smallholder farming currently exists side by side with large-scale, industrial agriculture, as an outcome of the Green Revolution unfolding in uneven and dualistic terms. In Guatemala's Pacific lowlands, state incentives fuel expansion of industrial export agriculture. Large-scale sugarcane production has come to surround rural farming communities, where small-scale farmers grow maize and sesame with little state support. Drawing on a survey of nearly 200 households, seventeen in-depth interviews, and four focus groups in five communities during 2014 and 2015 in the Department of Retalhuleu, our research explores the realities and imaginaries of smallholders as they negotiate their incorporation into the Green Revolution. In the face of minuscule agricultural plots resulting in limited production, cycles of agrarian debt, vulnerability to drought, and emigration to the United States, smallholders paradoxically work hard to replicate "modern" Green Revolution approaches in their own parcels. We argue that the proximal, uneven expansion of modern technocentric agriculture, fueled by the model of the Green Revolution, has helped cultivate "constrained spatial imaginaries" among smallholders, in which ideas and desires around improved agricultural practices remain bound to accessing hybrid seeds, chemical inputs, and technical extension, despite the way the Green Revolution has been implicated in their ongoing marginalization.